Plant neighbour identity matters to belowground interactions under controlled conditions. - Armas, Cristina; Pugnaire, Francisco Ignacio (PloS one, 2011)
Root competition is an almost ubiquitous feature of plant communities with profound effects on their structure and composition. Far beyond the traditional view that plants interact mainly through resource depletion (exploitation competition), roots are known to be able to interact with their environment using a large variety of mechanisms that may inhibit or enhance access of other roots to the resource or affect plant growth (contest interactions). However, an extensive analysis on how these contest root interactions may affect species interaction abilities is almost lacking.
The following values have no corresponding Zotero field: accession-num: 22114696
Keywords: biomass; citation; Ecosystem; Environment; Plant Development; Plant Roots; Plant Roots: growth & development; Species Specificity

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl237
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl23710.1093/jxb/erl237The following values have no corresponding Zotero field: accession-num: 17229759
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R.; Perotto, S.; Girlanda, M.; Vidano, G.; Luppi, a M. (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd accession-num: 11050558
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology

Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R; Perotto, S; Girlanda, M; Vidano, G; Luppi, a M (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology